Higher vitamin B6 dietary consumption is associated with a lower risk of glaucoma among United States adults - Yang, Ziling; Zhang, Jinming; Zheng, Yajuan (Frontiers in Nutrition, 2024)
Objective: Although numerous studies have substantiated the neuroprotective effects of vitamin B6 on the optic nerve and its enhancement of visual function, comprehensive data delineating the correlation between vitamin B6 and glaucoma at a national demographic scale remain insufficient. This study is designed to explore the link between the dietary consumption of vitamin B6 and glaucoma.Methods: This study included 3,850 individuals aged 40 and older from the National Health and Nutrition Examination Survey (NHANES), spanning 2005-2008. Dietary consumption of vitamin B6 was calculated from the average of two 24-hour dietary recall interviews. Glaucoma was diagnosed in accordance with the established Rotterdam criteria. To evaluate the relationship between vitamin B6 dietary consumption and the risk of glaucoma, we employed Restricted Cubic Splines and weighted multivariable logistic regression analysis. We employed stratified and three other sensitivity analyses to confirm the robustness of our results, and conducted a preliminary exploration of the potential association between vitamin B6 supplement consumption and glaucoma risk.Results: After adjusting for covariates, we found a significant inverse correlation between dietary consumption of vitamin B6 and glaucoma risk (p non-linearity=0.18; p for trend=0.02). Stratified analysis and three other sensitivity analyses revealed stability in the outcomes (all p for interaction>0.05). Compared to the lowest quartile of consumption (≤1.23 mg/day), individuals in the highest quartile of vitamin B6 consumption (>2.34 mg/day) experienced a 75% reduction in glaucoma risk (OR = 0.25, 95% CI 0.07-0.92). However, the effect of vitamin B6 supplements on glaucoma was inconclusive.Conclusions: A diet high in vitamin B6 inversely correlates with glaucoma risk, suggesting that increasing dietary intake of vitamin B6 could be a viable preventative strategy against glaucoma among adults in the United States.